(untitled) (Research, Society and Development, 2022)
Cerebrovascular accident (CVA) is characterized by the development of clinical disturbances of brain function. Divided into two groups: ischemic CVA due to arterial obstruction and hemorrhagic CVA due to blood vessel rupture. Health education is essential for prevention, as people informed about the disease will have greater adherence to preventive actions and will collaborate to reduce the pathology. Thus, we aimed to identify the influence of health education to reduce the CVA occurrence and the main risk factors causing the pathology. This is an exploratory, descriptive research with a qualitative approach, carried out with CVA patients hospitalized at regional hospital in Iguatu/CE. Data were analyzed using the patient questionnaire. This research was developed according to ethic norms 510/2016 and 466/2012 and previously approved by Ethics and Research Committee of Universidade Regional do Cariri CAAE: 43361121.9.0000.5055. It was possible to identify how health education is essential to reduce the occurrence of CVA and age, sex, ethnicity, sedentary lifestyle, smoking, alcohol consumption and heredity are the main causes of the disease. It was observed that most of the participants did not have knowledge about and how to prevent the CVA and, thus, it was noted the necessity and relevance of health education to encourage the change of modifiable risk factors for CVA and thereby collaborate to reduce involvement by the pathology.